2013
DOI: 10.1007/s10661-013-3062-1
|View full text |Cite
|
Sign up to set email alerts
|

Total and available heavy metal concentrations in soils of the Thriassio plain (Greece) and assessment of soil pollution indexes

Abstract: The Thriassio plain is located 25 km west of Athens city, the capital of Greece. Two major towns (Elefsina and Aspropyrgos), heavy industry plants, medium to large-scale manufacturing, logistics plants, and agriculture comprise the main land uses of the studied area. The aim of the present study was to measure the total and available concentrations of Cr, Zn, Ni, Pb, Co, Mn, Ba, Cu, and Fe in the top soils of the plain, and to asses soil contamination by these metals by using the geoaccumulation index (I geo),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 23 publications
5
65
3
Order By: Relevance
“…causing air, soil and groundwater pollution. Soil studies, which have been conducted in the area of Thriasion plain, have recorded high loads of heavy metals in soil horizons resulting in surface-and groundwater pollution by mobilizing them (Massas et al, 2013). Previous hydrogeological investigations in the study area have shown intense salinization of groundwater, in both coastal and inland region, where the front of seawater intrusion is detected in about 8.5 km away from the coast.…”
Section: Introductionmentioning
confidence: 85%
“…causing air, soil and groundwater pollution. Soil studies, which have been conducted in the area of Thriasion plain, have recorded high loads of heavy metals in soil horizons resulting in surface-and groundwater pollution by mobilizing them (Massas et al, 2013). Previous hydrogeological investigations in the study area have shown intense salinization of groundwater, in both coastal and inland region, where the front of seawater intrusion is detected in about 8.5 km away from the coast.…”
Section: Introductionmentioning
confidence: 85%
“…Different fractions of heavy metal in the soils have distinct availabilities [20,21]. Several differences were found among the speciation distributions of the different heavy metals, and the percentages of the different heavy metal fractions in the sugarcane soils are shown in Fig.…”
Section: Available Heavy Metal Forms Variationmentioning
confidence: 96%
“…Significant changes in the heavy metal concentration were mainly found on the surface layer, where amendments were applied and roots grew. However, the solubility and bioavailability of trace elements can be more important in remediation studies than the total or pseudo-total concentrations of these elements in the contaminated sugarcane soil, because they represent the most labile fractions subject to leaching as well as uptake by plant and microorganisms [20,21].…”
Section: Heavy Metal Concentrations Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…He soil contamination of heavy metals is now a worldwide environmental issue (alloway 1990;Bacon et al 2005;ettler et al 2004;ioannis et al 2013;Saba et al 2015), and this problem is especially severe in many developing countries (Wei et al 2010;Yaylal et al 2011;Mireles et al 2012;hu et al 2013;Fujimori et al 2014). heavy metal pollution can cause soil quality deterioration, as well as a reduction in crop yield and agricultural products' quality, which negatively affects the ecosystem and lives of animals and humans (nagajyoti et al 2010;Sardar et al 2010;Takashi et al 2014;anastasis et al 2014).…”
Section: Introduction Tmentioning
confidence: 99%